2010
DOI: 10.3109/10715762.2010.540575
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate peroxidase activity of cytochromec

Abstract: The peroxidase-type reactivity of cytochrome c is proposed to play a role in free radical production and/or apoptosis. This study describes cytochrome c catalysis of peroxide consumption by ascorbate. Under conditions where the sixth coordination position at the cytochrome c heme iron becomes more accessible for exogenous ligands (by carboxymethylation, cardiolipin addition or by partial denaturation with guanidinium hydrochloride) this peroxidase activity is enhanced. A reaction intermediate is detected by st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Acting on the hypothesis that this fourth species may be the missing ferryl (detected so clearly in the Mb experiments), an attempt was made to alter the distal pocket of Hb by increasing its solvent accessibility using controlled concentrations of a denaturing agent. This strategy was previously shown to be efficient in the case of cytochrome c [ 41 ], where it allowed accumulation of a ferryl species in the reaction with hydrogen peroxide. Figure 2 b thus shows UV-vis spectra of guanidine-treated oxy Hb upon mixing with nitrite.…”
Section: Resultsmentioning
confidence: 99%
“…Acting on the hypothesis that this fourth species may be the missing ferryl (detected so clearly in the Mb experiments), an attempt was made to alter the distal pocket of Hb by increasing its solvent accessibility using controlled concentrations of a denaturing agent. This strategy was previously shown to be efficient in the case of cytochrome c [ 41 ], where it allowed accumulation of a ferryl species in the reaction with hydrogen peroxide. Figure 2 b thus shows UV-vis spectra of guanidine-treated oxy Hb upon mixing with nitrite.…”
Section: Resultsmentioning
confidence: 99%
“…This process monitors the formation of conjugated lipid dienes at 235 nm. Thus, the antioxidant capacity of the tested extract, reflected in the delay of lipid peroxidation, is considered to be based on the same mechanism found in HAPX: the interaction of antioxidants with ferryl hemoglobin, generated in this case by cytochrome c [14]. In this assay, the extract blocked the process of lipid peroxidation for the whole duration of the experiment (700 min), as can be observed in Figure 2.…”
Section: Resultsmentioning
confidence: 83%
“…Consequently, the Michaelis constant K M accounts for the affinity of H 2 O 2 for the heme center, whereas the maximum rate achieved by the catalytic reaction, V max , accounts for the reactivity of ferryl compound I or II toward the Gc substrate. Recent spectroscopic and kinetic studies confirmed the involvement of the ferryl heme group in the PA of cytc 19. 20…”
Section: V0 Vmax Km Vmax/km and Pa Values[a] For The Oxidation Ofmentioning
confidence: 91%